Dynamic relationships among winning in various sports and donations to collegiate athletic departments - Reynolds, Ryan (Cogent social sciences, 2017)
A dynamic system consisting of donations and various sports’ success is estimated to examine relationships among winning and donations. Differences between Power 5, Non-power 5, and Football Championship Series alignments exist. Evidence that successful athletic programs have a positive impact on donations is found regardless of the conference alignment, but the impact varies by sport and alignment. The effects, however, are short lived. Donations, however, appear to have little impact on winning. There is some degree of interaction among winning in different sports.